Comparison of Furfural Production from Corn Waste and Empty Fruit Bunch (EFB): Effect of Time, Temperature, and Solvent - Muryanto; M Fadil MK Rongan; Tasrikin Agustianto; Eka Triwahyuni; Muhammad Arifuddin Fitriady; Teuku Beuna Bardant; Sri Sugiwati; Roni Maryana; Yanni Sudiyani; Misri Gozan (ASEAN Journal of Chemical Engineering, 2025)
Furfural is a compound derived from xylose, a building block material. Sources of furfural can come from various corn industry wastes such as corn cobs and corn husks, and palm oil industry wastes like Empty Fruit Bunch (EFB). This study aims to compare the potential of furfural production from corn industry waste and palm oil industry waste. The research method involves the hydrolysis and dehydration of hemicellulose using two types of solvents, sulfuric acid (SA) and Deep Eutectic Solvents (DES), at varying temperatures (160 °C, 170 °C, and 180 °C) and reaction times (60, 120, and 180 minutes). The highest furfural yield from corn cobs, 7.69 g/L, was obtained using 1 M sulfuric acid solvent at 160 °C for 60 minutes. The optimal condition for producing a high concentration of furfural from corn cobs was achieved using DES at 170°C for 60 minutes, yielding approximately 13.18 g/L. In contrast, furfural production from EFB resulted in a concentration of 4.70 g/L.